Building Coalitions: Extra Resources for Coalitions - Penne Smith; Gregory P. Siek; Elizabeth B. Bolton; Lisa Guion (EDIS)
This document is FY500, Part 8 of the 16 part series adapted for use in Florida by Elizabeth B. Bolton and Lisa Guion. Reprinted with permission March, 1997. Revised April, 2002.